Effect of an experimental surface treatment on Y-TZP zirconia flexural strength - Gómez, B. C.; Cortés-Rodríguez, C. J.; Calle, M. L. (Revista Mexicana de Ingenieria Biomedica, 2017)
Objective: To analyze the effect of surface micro shot peening as an experimental regeneration treatment on the flexural strength and residual stresses of a Y-TZP Zirconia, once it has been altered with other mechanical treat-ments such as micro sandblasting and milling. Methods: A total of 75 Zirconia Y-TZP specimens were divided into five n = 15 groups and subjected to surface treatments such as: milling and micro sandblasting (Groups 2 and 4) micro sandblasting + micro shot peening; and milling + micro shot peening (Groups 3 and 5), compared to a control group (Group 1), by X-ray diffraction (XRD), scanning electron microscopy (SEM), confocal microscopy (CLSM) and subjected to failure in a universal testing machine. All the results were compared to find a statistical relationship be-tween them using a mixed linear model and Tuckey. Results: The groups of micro shot peening and micro sandblas-ting presented a significant increase of the flexural strength p = 0.0082 vs the milling group. The XRD technique is not related to flexural strength measurements. Significance: It is possible that the micro shot peening be considered a treatment to regenerate the mechanical properties reduced by milling or sandblasting in Zirconia Y-TZP.